Seroprevalence of Borrelia burgdorferi, B. miyamotoi, and Powassan Virus in Residents Bitten by Ixodes Ticks, Maine, USA - Robert P. Smith; Susan P. Elias; Catherine E. Cavanaugh; Charles B. Lubelczyk; Eleanor H. Lacombe; Janna Brancato; Hester Doyle; Peter W. Rand; Gregory D. Ebel; Peter J. Krause (Emerging Infectious Diseases, 2019)
We conducted a serosurvey of 230 persons in Maine, USA, who had been bitten by Ixodes scapularis or I. cookei ticks. We documented seropositivity for Borrelia burgdorferi (13.9%) and B. miyamotoi (2.6%), as well as a single equivocal result (0.4%) for Powassan encephalitis virus.